Cardio-Oncology - Carver, Joseph; Minotti, Giorgio; Lipshultz, Steven E.; SpringerLink (Online service) (London : BioMed Central : Imprint: BioMed Central.)
The mission of Cardio-Oncology is to promote the science, technology, practice, and betterment of the public health of the emerging field of cardio-oncology. We are an international, open access journal that strives to publish original, important, valid, peer-reviewed articles on a diverse range of medical topics related to cardiovascular effects of cancer treatments. The journal welcomes submissions related to the pathophysiology, prevention, diagnosis, and treatment of the effects of cancer therapies, from basic mechanistic studies, to translational, preclinical and clinical research, including clinical trials, outcomes studies, case reports, and imaging techniques. Topical areas include, but are not limited to: Preclinical and clinical mechanisms of the cardiotoxicity of anticancer drugs; Biomarkers and the susceptibility of cancer patients to cardiovascular injury; Cancer treatment for patients with a cardiovascular history; Monitoring and detection of patients at risk of cardiotoxicity; Prevention and treatment strategies, such as dose changes for chemotherapy; Cardiovascular care for cancer survivors; Quality, safety, human factors and reliability of cancer care; Health systems design and strengthening. Cardio-Oncology is the premier journal devoted exclusively to this emerging specialty, providing an international forum for elevating the quality of medical care, disease prevention, and research via state-of-the-art reviews, filling a critical gap in the science and clinical practice of this important field. The journal serves to inform readers about the various aspects of cardio-oncology medicine and public health, including cultural, sociopolitical, ethical, legal, environmental, economic, structural, and historical issues. We are committed to producing a high impact and credible publication that is timely and enjoyable to read.
Keywords: Oncology; Cardiology; Oncology; Cardiology